Duality Role of Chief Executive Officer (CEO) in Corporate Governance and Performance of Quoted Companies in the Nigerian Stock Exchange: An Appraisal of the Perception of Managers and Accountants (Global Journal of Management and Business Research, 2014)
The Chief Executive Officer (CEO) of a corporate entity is its Chief Accounting Officer. He is at the head of management which according to Miller (2005) is more of hands on activity; conducting and supervising actions with the judicious use of means to accomplish certain goal/s. The Chairman of the Board of Directors on the other hand is the chief policy or law maker of the enterprise. CEO Duality occurs when the CEO is equally the Chairman of the company or Board of Directors. Since the position of a CEO is a critical element of corporate governance of a company, a combination of the roles of CEO and chairman of the company could have far reaching implications on stewardship accounting and corporate governance and by extension corporate performance. Poor corporate governance has been implicated in most corporate failures in and outside Nigeria. Hence this paper appraises the practice of CEO Duality in Nigeria and examines its implications on effective corporate governance and performance of Non-Financial companies in the Nigerian Stock Market. It uses panel data on the performances (ROE) of companies with CEO-Duality and those without CEO-Duality to determine the effect of this duality on company performance. A sample size of 30 companies selected through the Taro Yameni formula was used while their performances (ROE) for the years 2006 to 2010 were equally used without further sampling. A test of significant difference was performed using the E-view statistics. It was discovered that there is a significant difference between the performances of companies with CEO duality and those without CEO duality. Again the average performance of the former was statistically and significantly lower than the average performance of the later. It was therefore recommended that as a veritable means of strengthening corporate governance and enhancing performance, CEO duality should be minimized/reduced as much as possible. Chairmen of companies should not double as Chief Executive Officers.
Keywords: chief executive officer; chairman of the board; stewardship accounting; corporate performance